ChemInform Abstract: Synthesis of Indolines via Pd(II)‐Catalyzed Amination of C—H Bonds Using PhI(OAc)2 as the Bystanding Oxidant. Issue 47 (4th November 2013) - Mei, Tian‐Sheng; Leow, Dasheng; Xiao, Han; Laforteza, Brian N.; Yu, Jin‐Quan
Abstract A novel protocol for the title synthesis via a palladium‐catalyzed C—H activation/cyclization sequence is developed.